Effects of terrorism threat levels collaborating stereotypes, stigmatization and prejudices on perceived interpersonal social support in the reintegration of ex-detained suspected terrorists into the community - Shammah, Monday L.V. (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article gives important information about effects of terrorism threat levels collaborating stereotypes, stigmatization and prejudices on perceived interpersonal social support in the reintegration of ex-detained terrorism suspects into the community. The main aim of this research is to examine what effects is embedded in terrorism threat levels collaborating stereotype, stigmatization and prejudice on perceived social support in the reintegration of ex-detained suspected terrorists into the community’?. Sixty participants drawn from Kuchigoro Terrorism Internal Displaced Peoples’ Camp (TIDPC), Abuja, Nigeria were used for the study. A modified version of “Interpersonal Social Support Evaluation List: shortened version – 12 items” was used for the collection of data. One-Way Analysis of Variance (ANOVA) was used to analyze the data. Results indicated significant effects, F (5, 54 = 3.223, P = 0.05). This means terrorism threat levels collaborates stereotypes, stigmatization and prejudices impact on the type of interpersonal social support given to ex-detained suspected terrorists by members of the Community during their reintegration into the community. It was observed and recommended that, there is dire need of deliberate creation of terrorism education awareness and application of psychological interventions, as well as putting in place a mechanism for the resolution of interpersonal conflicts among members of the community. The study’s results imply that, the training programs of Correctional Services Personnel should include rehabilitation and reintegration skills.